Patellofemoral arthroplasty in combination with high tibial osteotomy can achieve good outcome for patients with medial-patellofemoral osteoarthritis - Peng, Yonggang; Lin, Wei; Zhang, Yufeng; Wang, Fei (Frontiers in Surgery, 2022)
Background: The purpose of our study was to report the clinical and functional outcomes in patients undergoing patellofemoral arthroplasty(PFA) in combination with a high tibial osteotomy(HTO). In consideration of its conservative and kinematics-preserving characteristics, we hypothesized that PFA in combination with HTO would give rise to better clinical and functional outcomes in medial and patellofemoral compartment osteoarthritis (MPFOA). Methods: From January 2018 to April 2020, the patients who underwent PFA in combination with HTO for MPFOA were included in the study. The clinical data were analyzed using the Knee Society Score, Oxford Knee Score, Range of Motion, and Forgotten Joint Score after the procedure. Radiological evaluations were performed to assess the tibiofemoral osteoarthritis progression and implant loosening. For all tests, the value of p <0.05 was considered statistically significant. Results: A total of 9 consecutive patients who underwent PFA in combination with HTO were included. 2 cases were males and 7 cases were females. The average follow-up period was 2.6±0.4(range 2-3.4) years. Clinical outcomes showed a significant improvement in the knee range of motion, Oxford Knee Score, and Knee Society Score at the last follow-up. And the Forgotten Joint Score showed excellent clinical outcomes (71.2±10.2) at the final follow-up. We found no complications during the follow-up time. Conclusion: Patients who underwent PFA in combination with HTO for the treatment of MPFOA achieved excellent clinical and radiological results in an average follow-up of 2.6 years. Therefore, we believe that this surgical approach is an effective and reliable treatment for patients with MPFOA.